2021
DOI: 10.1167/jov.21.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Look where you go: Characterizing eye movements toward optic flow

Abstract: When we move through our environment, objects in the visual scene create optic flow patterns on the retina. Even though optic flow is ubiquitous in everyday life, it is not well understood how our eyes naturally respond to it. In small groups of human and non-human primates, optic flow triggers intuitive, uninstructed eye movements to the focus of expansion of the pattern (Knöll, Pillow, & Huk, 2018). Here, we investigate whether such intuitive oculomotor responses to optic flow are generalizable to a larger g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Therefore, vection is seen as a possible way to alleviate cybersickness (Stanney et al, 2020b). Vection doesn't seem causal to visually induced motion sickness (Kuiper et al, 2019;Chow et al, 2021). A large Field of view can impact vection (de Winkel et al, 2018;van der Veer et al, 2019).…”
Section: Vectionmentioning
confidence: 99%
“…Therefore, vection is seen as a possible way to alleviate cybersickness (Stanney et al, 2020b). Vection doesn't seem causal to visually induced motion sickness (Kuiper et al, 2019;Chow et al, 2021). A large Field of view can impact vection (de Winkel et al, 2018;van der Veer et al, 2019).…”
Section: Vectionmentioning
confidence: 99%
“…This experimental protocol not only requires orders of magnitude less time compared to traditional psychophysical methods, but participants report it to be more natural, making it more suitable for untrained subjects and potentially children and infants. Similar approaches have recently been used to measure contrast sensitivity ( Mooney et al, 2018 ), eye movements toward optic flow ( Chow et al, 2021 ), or retinal sensitivity ( Grillini et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knoll et al showed that in both human and nonhuman primates, optic flow triggers intuitive and uninstructed eye movements toward the FOE [59]. Chow et al performed an experiment in which the subjects viewed expanding or contracting optic flow made by moving dots that could randomly shift [60]. The authors found that 84% of observers tracked the FOE with their eyes without being instructed to do that.…”
Section: -2-eye Movements and Optic Flowmentioning
confidence: 99%